Ketika Bahasa Ibu Menjadi Asing: Penggunaan Bahasa Sunda pada Anak Usia Dini di Era Digital - Mita Maulida; Elan Elan; Qonita Qonita (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to explore the declining use of Sundanese language among early childhood children in West Java within the context of the digital era. The research employed a qualitative phenomenological approach, collecting data through semi-structured interviews with ten participants, including early childhood educators and parents of children aged 3–6. The findings reveal several factors contributing to the reduced use of Sundanese, such as the dominance of Indonesian at home, the influence of socially diverse environments, and the intense exposure to digital media in Indonesian and foreign languages. Sundanese is perceived as a second or even foreign language by many children due to the lack of natural interaction in their daily lives. Efforts to preserve Sundanese remain limited to ceremonial programs such as